2020
DOI: 10.1155/2020/4147357
|View full text |Cite
|
Sign up to set email alerts
|

Green Synthesis of ZnO-GO Composites for the Photocatalytic Degradation of Methylene Blue

Abstract: Beneficial from the excellent optical performance of zinc oxide (ZnO) nanocrystals and the absorption properties of graphene oxide (GO), the nanocomposites of ZnO and GO with synergistic photocatalytic effects were prepared by a precipitation method, in which GO is utilized as the catalyst carrier. The prepared composites were characterized by X-ray diffraction, X-ray photoelectron spectroscopy, UV-vis spectroscopy, field emission scanning electron microscopy, and transmission electron microscopy and also perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(12 citation statements)
references
References 49 publications
3
9
0
Order By: Relevance
“…Therefore, from the Raman spectra, it is observed that there is the attachment of ZnONPs or AgNPs onto the GO matrix leading to partial restoration of the sp 2 network. Both these results are consistent with previous reports on the Raman spectra of AgNPs|GO and of ZnONPs|GO [34] [35] [36].…”
Section: Raman Spectroscopysupporting
confidence: 94%
See 1 more Smart Citation
“…Therefore, from the Raman spectra, it is observed that there is the attachment of ZnONPs or AgNPs onto the GO matrix leading to partial restoration of the sp 2 network. Both these results are consistent with previous reports on the Raman spectra of AgNPs|GO and of ZnONPs|GO [34] [35] [36].…”
Section: Raman Spectroscopysupporting
confidence: 94%
“…and GO through the modification of the fundamental process of electron-hole pair formation. Although these findings are very similar to those reported by Lin et al, 2020 [34]; the two extracts used in this study caused lower wavelength readings as opposed to their study where a precipitation method was used to synthesize ZnONPs|GO. This is also noteworthy due to the small nature of the nanoparticles produced in this study.…”
Section: Ultraviolet-visible Spectroscopy (Uv-vis)supporting
confidence: 90%
“…As shown in the inset of Figure 9A, the presence of a peak at around 271 nm reflects the n-π* transitions of C=O bonds (π-plasmon) of graphene oxide verifying the existence of GO. 37 Also, The absorbance refers to a strong peak that appeared at 376 nm, which is attributed to the O 2p -Zn 3d transition of ZnO, 76 the fundamental transition in ZnO from the valence band to the conduction band. It easily can be noticed a slight red-shift in the absorption edge of ZnO when alloying with Al that reflects the variation of the band gap.…”
Section: Insight Into Optical Propertiesmentioning
confidence: 99%
“…The GO is a superior electron collector together with excellent transporter and thus minimizes the recombination of electron‐hole pairs generated from ZnO. Based on these exciting properties, numerous attempts have been interested in investigating the ZnO/GO nanocomposites 37,38 . However, by far, we have a lack of basic and applied information on the impact of Al on the ZnO‐GO nanocomposites.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation